Arboretum and Puerto Almendras viruses: two novel rhabdoviruses isolated from mosquitoes in Peru - Vasilakis, Nikos (Society for General Microbiology, 2014)
Arboretum virus (ABTV) and Puerto Almendras virus (PTAMV) are two mosquito-associated rhabdoviruses isolated from pools of Psorophora albigenu and Ochlerotattus fulvus mosquitoes, respectively, collected in the Department of Loreto, Peru, in 2009. Initial tests suggested that both viruses were novel rhabdoviruses and this was confirmed by complete genome sequencing. Analysis of their 11 482 nt (ABTV) and 11 876 (PTAMV) genomes indicates that they encode the five canonical rhabdovirus structural proteins (N, P, M, G and L) with an additional gene (U1) encoding a small hydrophobic protein. Evolutionary analysis of the L protein indicates that ABTV and PTAMV are novel and phylogenetically distinct rhabdoviruses that cannot be classified as members of any of the eight currently recognized genera within the family Rhabdoviridae, highlighting the vast diversity of this virus family.